Effects of Plasmodium vivax malaria in pregnancy. - Nosten, F; Mcgready, R; Simpson, J; Thwai, K; Balkan, S; Cho, T; Hkirijaroen, L; Looareesuwan, S; White, N (1999)
BACKGROUND: Plasmodium vivax is more common than P. falciparum as a cause of malaria in many parts of the tropics outside Africa. P. falciparum infection has harmful effects in pregnancy, but the effects of P. vivax have not been characterised. We investigated the effects of P. vivax infection during pregnancy. METHODS: Since 1986, pregnant Karen women living in camps for displaced people on the western border of Thailand have been encouraged to attend antenatal clinics. Karen women were screened for malaria and anaemia at each week of pregnancy until delivery, and pregnancy outcome recorded. We compared the effects of P. vivax infection on anaemia and pregnancy outcome with those of P. falciparum and no malaria infection in the first pregnancy recorded at the antenatal clinics. FINDINGS: There were 634 first episodes of pure P. vivax malaria in 9956 women. P. vivax malaria was more common in primigravidae than in multigravidae and was associated with mild anaemia and an increased risk of low birthweight (odds ratio 1.64 [95% CI 1.29-2.08], p<0.001). The birthweight was a mean of 107 g (95% CI 61-154) lower in women with P. vivax infection than in uninfected women. By contrast with P. falciparum malaria, the decrease in birthweight was greater in multigravidae. P. vivax malaria was not associated with miscarriage, stillbirth, or with a shortened duration of pregnancy. INTERPRETATION: P. vivax malaria during pregnancy is associated with maternal anaemia and low birthweight. The effects of P. vivax infection are less striking than those of P. falciparum infection, but antimalarial prophylaxis against P. vivax in pregnancy may be justified.